How Spiritual Leadership Boosts Nurses’ Work Engagement: The Mediating Roles of Calling and Psychological Capital - Wu, Wei-Li; Lee, Yi-Chih (International journal of environmental research and public health, 2020)
Work engagement is an important topic in the field of nursing management. Meanwhile, spiritual leadership has been demonstrated to have a positive impact on healthcare workers. However, the relationship between spiritual leadership and work engagement is unclear. The main purpose of this study was to investigate the influence of spiritual leadership on work engagement through increased spiritual well-being and psychological capital. This study used a cross-sectional survey to collect data in Taiwan. The sample included 164 nurses, with empirical testing carried out by PROCESS Macro for SPSS. The results show that spiritual leadership has a positive influence on work engagement and that spiritual well-being (i.e., calling) and psychological capital mediate the effect of spiritual leadership on work engagement. According to the results of this study, nursing leaders must be aware of the role of spiritual leadership in promoting work engagement.